2001
DOI: 10.1007/bf03343941
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of incidentally discovered adrenocortical adenomas: A retrospective evaluation

Abstract: Adrenal adenoma is the most frequent lesion among adrenal incidentalomas. The present retrospective study was undertaken to investigate medium-term evolution of supposed or ascertained adrenocortical adenomas in a group of 53 subjects (16 males and 37 females, aged 31-83 yr), with bilateral (no.=8) or monolateral (no.=45) incidentally discovered adrenal masses (size 10-50 mm, median 25 mm), who were followed-up for 6-78 months (median 24 months). Diagnosis of adenoma was based on size and morphovolumetric aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
39
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 21 publications
11
39
1
Order By: Relevance
“…Newly diagnosed subtle endocrine alterations appeared in 28% of the patients, most of them featuring a decrease in DHEA-S and ACTH levels, as previously reported (14,15). Similar small changes in hormonal function have been reported by Barzon et al (14) and Grossrubatscher et al (15).…”
Section: Discussionsupporting
confidence: 84%
“…Newly diagnosed subtle endocrine alterations appeared in 28% of the patients, most of them featuring a decrease in DHEA-S and ACTH levels, as previously reported (14,15). Similar small changes in hormonal function have been reported by Barzon et al (14) and Grossrubatscher et al (15).…”
Section: Discussionsupporting
confidence: 84%
“…Terzolo et al (87) reported a spontaneous endocrine normalization in 50% of patients with subclinical hypercortisolism, whereas no patient developed clinical Cushing's syndrome. At variance, in other reports subclinical hypercortisolism persisted throughout follow-up or became clinically evident in some patients (62,67,83,90,104,116). In our experience, one out of eight patients with subclinical Cushing's syndrome at diagnosis developed overt Cushing's syndrome during follow-up (53).…”
Section: Hormone Productioncontrasting
confidence: 58%
“…Whether these features, which are typical of the metabolic syndrome, will have an impact on the long-term morbidity of patients with subclinical Cushing's syndrome remains to be determined. Long-term perspective studies are lacking; however, an amelioration of clinical or biochemical abnormalities in patients with subclinical hypercortisolism after surgery has been reported (42,51,53,66,67,(88)(89)(90). Improvement of blood pressure, obesity, metabolic abnomalities, collagen and bone turnover markers was observed after adrenalectomy in patients with subclinical Cushing's syndrome (51,66,67).…”
Section: Hormone Productionmentioning
confidence: 99%
“…Barzon et al (1999) reported that incidentalomas tend to undergo a period of increase in mass size but thereafter remain unchanged, suggesting the possible existence of a programmed end point of growth of adrenal masses. In contrast, Grossrubatscher et al (2001) found that adrenal mass enlargement may occur unpredictably at any time, sometimes after a long period of 'quiescence'. In the present study we noted frequent increments but also reductions in mass size, although such variations consistently proved to be small.…”
Section: Discussionmentioning
confidence: 94%
“…Other authors have similarly reported the development of overt hypersecretion of the mass over time and even occasional malignant transformation of adrenal incidentalomas (Hensen et al, 1990;Jockenhovel et al, 1992). In contrast, no shift toward malignancy or functional hyperactivity was observed in several other studies (Osella et al, 1994;Barry et al, 1998;Terzolo et al, 1998;Rossi et al, 2000;Siren et al, 2000;Grossrubatscher et al, 2001). Thus, the natural course of adrenal incidentalomas still requires further clarification.…”
Section: Discussionmentioning
confidence: 95%